PARAMETERS EXTRACTION OF A DOUBLE-DIODE MODEL OF PHOTOVOLTAIC CELL USING NEWTON-RAPHSON METHOD (FULafia Journal of Science and Technology, 2023)
The mathematical modeling of solar cells is essential for any optimal knowledge of the operation efficiency or diagnosis of photovoltaic cell. The photovoltaic module is generally represented by an equivalent circuit whose parameters are experimentally calculated by using the characteristic I-V. Determination of these parameters poses a challenge to researchers, manufacturers and the end-user, making the characterization of the PV module difficult. Hence, parameters extraction of double diode model of PV cell was embarkedupon. Double diode model was chosen because of its better accuracy compared to the single diode model. I-V characteristics equation of the model was used as the basis upon which Newton-Raphson method was used for estimating the parameters. In this research study, parameters of a double diode model (Iph, Io1, Io2, a1, a2, Rs and Rp) were found by obtaining seven different objective functions f1(x) to f7(x) and their derivatives with respect to the parameters. These derivatives of the objective functions were used to obtain the Jacobian matrix J(x). Newton-Raphson method was developed on software MATLAB/Editor to compute the parameters
Keywords: Photovoltaics; Double diode; Newton-Raphson; Jacobian matrix; MATLAB; Standard Test Condition